2014
DOI: 10.1179/1743284714y.0000000559
|View full text |Cite
|
Sign up to set email alerts
|

CRITICAL ASSESSMENT 1: Outstanding issues in crystallographic variant selection in displacive transformations

Abstract: Variant selection has been a well researched subject in metallurgy and materials science in recent decades. The emergence of experimental techniques capable of determining crystallographic orientation at the grain level has provided insight into the fundamental processes underlying variant selection. The theory, however, is far from complete. Fundamental questions, such as the specific roles of stress and strain in variant selection, have yet to be fully resolved. It remains unclear whether variant selection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…where U is interaction energy, τ is the shear stress resolved on the habit plane of a variant, σ is arising from the prior formed thicker martensite laths as shown in early studies [55,56]. Detailed review of variant selection is given by Kundu recently [58]. Gong et al suggested that a bainite transformation may be accelerated by ausforming [59].…”
Section: Microstructure After Tmt Processingmentioning
confidence: 99%
“…where U is interaction energy, τ is the shear stress resolved on the habit plane of a variant, σ is arising from the prior formed thicker martensite laths as shown in early studies [55,56]. Detailed review of variant selection is given by Kundu recently [58]. Gong et al suggested that a bainite transformation may be accelerated by ausforming [59].…”
Section: Microstructure After Tmt Processingmentioning
confidence: 99%
“…[4][5][6][7][8][9] A role of {100} cleavage fracture has been reported in line pipe steels. [10][11][12] Garcia-Junceda et al 13 found out an occurrence of delamination fracture associated with {100} cleavage plane in the hot extruded bar of 14CrODS steel. Kimura and Inoue 14 controlled the delamination fracture along the {100} cleavage plane in a low alloy steel formed by caliber-rolling during a tempering, and they attained extremely high absorbed energy at around room temperature, called inverse temperature dependence of toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of electromagnetic field to crystal orientation selection is an interesting topic. 45 It is reported that electropulsing causes sudden reduction of electrical resistance and change of atomic element distribution in packed oxide powders. 46 The observed change of electrical resistance proves not to be due to thermal effects but is rather dominated by field induced dielectric breakdown.…”
Section: Unclarified Effects Of Electropulsingmentioning
confidence: 99%
“…Implementation of electromagnetic field to crystal orientation selection is an interesting topic. 45…”
Section: Unclarified Effects Of Electropulsingmentioning
confidence: 99%